Analysis of Teachers' Capability to Choose PAI Learning Design Models - Siti Rochmah Dirgantini; Mulyawan Nugraha Saftwandi; Ujang Dedih (Zona Education Indonesia, 2023)
Learning design model is an important stage in a learning process because the learning model is the initial plan for achieving the educational goals. This research uses a descriptive method of surveys using simple random and data collection through questionnaires. This research aims to find out how the teacher's ability in choosing a learning design model. The result of this study is that PAI teachers' ability to choose a learning design model has a fairly good category. This corresponds to the largest percentage of results obtained through questionnaires related to the selection of learning design models, indicator one gets 57.9% teachers always consider the choice of a teaching design model, 50% teachers state that complexity of the material is difficult, 55.3% always consider a model of the teaching material according to the character, 42.1% always consider student maturity, 44.7% teachers sometimes choose the model of teaching materials according to their interests, 44,7% teachors always consider models of the lessons according to interest, 71.1 teachers occasionally use only one model of a teacher's design, 50% always use a model that is effective and efficient.